Differences in selected performance indicator between winning and losing team in rugby seven: Case study on vancouver world rugby 7 series 2016 / Tuan Nur Ainun Tuan Muda - Tuan Muda, Tuan Nur Ainun (Faculty of Sport Science and Recreation, 2016)
This cross sectional study conducted to determine the differences in selected performance indicator between winning and losing team in Vancouver World Rugby Series. Total of 45 matches in this tournament was analysing using hand notational analysis in the form of frequency table. Mann-Whitney Test was used to determine the differences in selected performance indicator between winning and losing team. There were five significant indicators (try score, conversion, lineout lost, line brake and turnover won) from overall eighteen performance indicator that used in this study.